HISTORIOGRAPHY AND SOURCE STUDY OF JADIDISM IN DAGESTAN - Navruzov, Amir Ramazanovic; Sihaliev, Samil' Sihalievic (History, Archeology and Ethnography of the Caucasus, 2024)
A review of the historiography of the development of Jadidism and Muslim reformism in the Volga region, Central Asia, Transcaucasia and the study of Arabographic sources on the North-Eastern Caucasus allowed us to agree with the conclusion of a number of Western scholars who spoke not about Jadidism in the Russian Empire, but about various forms of Jadidism. Despite the wide range of ideas and concepts regarding the definition of this movement, the Dagestan sources nevertheless show a certain picture, which allows us to approach the term Jadidism of the 20th century somewhat cautiously. Despite the fact that the Dagestan sources mention the term «usul-i-jadid», as well as the fact that the Egyptian reformers and their Dagestani followers are called jadids in local sources, we still try not to use this term in relation to Dagestan. Here we can talk more about Muslim reformism than about Jadidism, since the discussion of various issues in Dagestan proceeded exclusively within the framework of the Muslim theological tradition, with a system of definitions, symbols, images and concepts characteristic of Islamic discourse. Contrary to what Soviet and modern historiography writes about the Dagestan reformers, they were not supporters of the secularization of society, they did not call for adaptation and perception of European culture. Moreover, their views, in addition to being purely Islamic, also reflected their call to return to an earlier period of Islam, when Muslim society was at its peak. Comparing the movement of Muslim reformers and the Jadids of the Volga region and Dagestan, one can note a number of similarities in the ideas of the Tatars al-Kursawi, al-Marjani and the Dagestanis al-Kuduki, al-Gumuki. All these scholars came up with similar ideas of ijtihad. At the same time, despite some contacts between the Dagestan reformers and Jadids of the 20th century, and some similarities of ideas in matters of education reform, nevertheless, Jadidism in the Volga region at the beginning of the 20th century and reformism in Dagestan were different.